2010
DOI: 10.1007/978-1-60761-609-2_19
|View full text |Cite
|
Sign up to set email alerts
|

LHRH-Targeted Nanoparticles for Cancer Therapeutics

Abstract: Synthesis and evaluation of a novel cancer cell's receptor-targeted internally quaternized and surface neutral poly(amidoamine) (PAMAM) generation four dendrimer as well as PAMAM-paclitaxel conjugate are described. The advantages of developed nanocarriers include but are not limited to (1) internal cationic charges for the complexation with small interfering RNA or antisense oligonucleotides and their protection from the degradation in systemic circulation; (2) neutral-modified surface for low cytotoxicity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…The height differences on the surface are indicated by the color code: lighter regions indicate higher heights. Complexes of siRNA with cationic liposomes, mesoporous silica nanoparticles, PAMAM and PPI dendrimers and SPIO nanoparticles were performed in our laboratory as previously described [16,[19][20][21][22][23][24].…”
Section: Methodsmentioning
confidence: 99%
“…The height differences on the surface are indicated by the color code: lighter regions indicate higher heights. Complexes of siRNA with cationic liposomes, mesoporous silica nanoparticles, PAMAM and PPI dendrimers and SPIO nanoparticles were performed in our laboratory as previously described [16,[19][20][21][22][23][24].…”
Section: Methodsmentioning
confidence: 99%
“…Dr. Minko pioneered in the use of peptide similar to luteinizing-hormone-releasing hormone (LHRH) as cancer targeting moiety for many different types of nanoparticles for treatment of different cancers. [2][3][4]8,11,[15][16][17][18] It was found that LHRH receptors are over expressed in plasma membrane of many types of cancer cells. In contrast, they do not express in healthy visceral organs and their expression in healthy tissues from reproductive organs is significantly less when compared with cancerous tissues.…”
Section: Liposomal Nanopreparationsmentioning
confidence: 99%
“…1 Delivery of anticancer drugs and imaging agents by nanoscale-based carriers allows for enhancing their uptake specifically by cancer cells, overcoming or suppressing drug resistance and limit adverse side effects upon healthy organs and tissues. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Polymeric and inorganic nanoparticles, liposomes, micelles, self-assemblies, lipid emulsions and prodrug conjugates have been recently defined as "nanopreparations." 19 This chapter presents an overview of a few nanopreparations implicated in cancer therapy and diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…Active targeting of tumor-specific surface receptors that are expressed or overexpressed uniquely on primary tumors was described previously using nanosized medicines (nanomedicines) for the treatment of primary tumors [4][5][6][7][8] and can also be applied for the treatment of metastases [9,10]. However, the genetic mutations that cancer cells undergo increase their resistance to chemotherapeutic agents [11] and, although nanomedicines can overcome some of the mechanisms responsible for this resistance [12], biological barriers such as the high interstitial pressure and the dense extracellular matrix within tumors [13] render their penetration into the tissue largely inefficient beyond the perivascular region [14][15][16].…”
Section: Introductionmentioning
confidence: 99%